Pengembangan media e-comic untuk menumbuhkan sikap tanggung jawab pada siswa di SD Negeri 1 Seulalah - Rinanda Ramadhani; Lhutfia Wahyu Safutri (Kajian Pendidikan, Seni, Budaya, Sosial dan Lingkungan, 2025)
This study aims to develop e-comic based learning media to foster a sense of responsibility for mutual cooperation in students at SD Negeri 1 Seulalah. E-Comic media was chosen because of its interactive and visual potential that is interesting for elementary school students, so it is expected to improve understanding and motivation to learn social character. The study used the ADDIE development model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observation, interviews, documentation, and question instruments distributed to 20 grade V students. The results of the analysis showed that e-comic media received a very good response with an average score of 96.75, which is included in the "very good" category. E-comic media has proven to be effective in conveying moral messages in an interesting, easy-to-understand way, and relevant to students' daily lives. The results of the study showed that the developed e-comic media is feasible to use and effective in fostering a sense of responsibility in mutual cooperation based on student responses. This media is recommended as an alternative learning media for Character Education in Elementary Schools.